y(y-3)=28

Simple and best practice solution for y(y-3)=28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(y-3)=28 equation:


Simplifying
y(y + -3) = 28

Reorder the terms:
y(-3 + y) = 28
(-3 * y + y * y) = 28
(-3y + y2) = 28

Solving
-3y + y2 = 28

Solving for variable 'y'.

Reorder the terms:
-28 + -3y + y2 = 28 + -28

Combine like terms: 28 + -28 = 0
-28 + -3y + y2 = 0

Factor a trinomial.
(-4 + -1y)(7 + -1y) = 0

Subproblem 1

Set the factor '(-4 + -1y)' equal to zero and attempt to solve: Simplifying -4 + -1y = 0 Solving -4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 0 + 4 -1y = 0 + 4 Combine like terms: 0 + 4 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4

Subproblem 2

Set the factor '(7 + -1y)' equal to zero and attempt to solve: Simplifying 7 + -1y = 0 Solving 7 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 0 + -7 -1y = 0 + -7 Combine like terms: 0 + -7 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7

Solution

y = {-4, 7}

See similar equations:

| y=-1.5*0+3 | | 6*0-2y=6 | | 6x-2*0=6 | | 7=12+10cosine(30t) | | Y^3-3y^2-4y=12 | | -2*0+y=11 | | 20y^2-4y^4= | | 20y^2-4y^4=0 | | -2x+0=11 | | in*(x)+in*(x+3)=in*4 | | 14x=x*3 | | 12y+8=44 | | -2(2b+3)+(5b-8)=0 | | 7x+5x+3+7=3x+4+8x | | 2x+10+48=180 | | 100[.03(p+3)]= | | 2p-5+2p-5+p+2+p+2=90 | | 9p+6p+8p+6p=48 | | x=9-5 | | x^4+2x^3-2x^2+2x^2+2x-3=0 | | 7x^3-6x^2-12x+8=0 | | 10x=52-3x | | X/2=19 | | t^4+8t^2+12=0 | | t^4+t^2+12=0 | | 3x=13-10x | | 2x=81-7x | | 10+(4*-1)= | | 2x+6=86-8x | | 7e+2f-5e= | | 16-(2y+4)+(6y-2)= | | 7x+6=96-3x |

Equations solver categories